Mutational signatures of redox stress in yeast single-strand DNA and of aging in human mitochondrial DNA share a common feature - Degtyareva, Natalya P. (PLoS Biol, 2019)
Redox stress is a major hallmark of cancer. Analysis of thousands of sequenced cancer exomes and whole genomes revealed distinct mutational signatures that can be attributed to specific sources of DNA lesions. Clustered mutations discovered in several cancer genomes were linked to single-strand DNA (ssDNA) intermediates in various processes of DNA metabolism. Previously, only one clustered mutational signature had been clearly associated with a subclass of ssDNA-specific apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC) cytidine deaminases. Others remain to be elucidated. We report here deciphering of the mutational spectra and mutational signature of redox stress in ssDNA of budding yeast and the signature of aging in human mitochondrial DNA. We found that the predominance of C to T substitutions is a common feature of both signatures. Measurements of the frequencies of hydrogen peroxide–induced mutations in proofreading-defective yeast mutants supported the conclusion that hydrogen peroxide–induced mutagenesis is not the result of increased DNA polymerase misincorporation errors but rather is caused by direct damage to DNA. Proteins involved in modulation of chromatin status play a significant role in prevention of redox stress–induced mutagenesis, possibly by facilitating protection through modification of chromatin structure. These findings provide an opportunity for the search and identification of the mutational signature of redox stress in cancers and in other pathological conditions and could potentially be used for informing therapeutic decisions. In addition, the discovery of such signatures that may be present in related organisms should also advance our understanding of evolution.